ANALISIS ASAP DAN EMISI GAS BUANG BUS BAGI KESEHATAN PETUGAS TICKETING HALTE - Yunita Primasanti; Atik Aryani (Jurnal Ilmu Keperawatan Indonesia (JIKI), 2022)
Motor vehicles emit a wide variety of gases and particles including a variety of high molecular weight organic and inorganic compounds that can be inhaled directly through the nose. Several components of air pollutants as primary pollutants include most of the other air pollutants that can affect air quality and can be grouped into CO, NO2, SO2, HC, and others. Initial observations made at the ticketing bus stop officers found that the officers did not wear perfect personal protective equipment when doing their work. The terminal is a transit point for public transportation modes such as buses. Stop ticketing officers are workers who work in an environment that is prone to smoke pollution and motor vehicle gas emissions. The purpose of this study is to create a work environment, especially ticketing station attendants that are safe, comfortable and able to improve the health and productivity of ticketing bus stop officers and analyze CO and SO2 exposure to ticketing bus stop workers' diseases. The study took data from 20 respondents, all of whom were ticketing bus stop officers at the Sumberlawang terminal, Sragen. The method used in this study is multiple linear regression which functions to measure the relationship between variables and test the research hypothesis. Then the results showed that the effect of SO2 exposure on pain had no significant effect on the disease of ticketing bus stop officers, because the condition of the bus had no significant effect. Buses that stop briefly at the bus stop are the average new bus. has zero emissions and emits less SO2.